Perspectives on Israel and the church : 4 views (B&H Publishing Group, 2015)
The relationship between Israel and the church is one of the most debated issues in the history of theology. Some hold the view that there is almost seamless continuity between Israel and the church, while others believe there is very little continuity. Additional perspectives lie between these two. This debate has contributed to the formation of denominations and produced a variety of political views about the state of Israel. To advance the conversation, Perspectives on Israel and the Church brings together respected theologians representing four positions: Traditional covenantal view by Robert L. Reymond; Traditional dispensational view by Robert L. Thomas; Progressive dispensational view by Robert L. Saucy; Progressive covenantal view by Chad Brand and Tom Pratt Jr. - Publisher.